2005
DOI: 10.1111/j.1744-6570.2005.681.x
|View full text |Cite
|
Sign up to set email alerts
|

How Social Dominance Orientation and Job Status Influence Perceptions of African‐american Affirmative Action Beneficiaries

Abstract: This paper examines evaluative judgments about an African‐American beneficiary of affirmative action (AA) in two studies. Based on a motivated social cognition model, we test whether the use of AA, social dominance orientation (SDO), and job status jointly influence judgments about the future job performance and career progression of an AA beneficiary. In a sample of 244 undergraduate business students, Study 1 showed that SDO and AA interact to predict job‐related performance expectations, and AA and job stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 52 publications
(125 reference statements)
0
31
0
Order By: Relevance
“…Those high in social dominance orientation believe in group hierarchies and Downloaded by [Florida Atlantic University] at 07:42 18 November 2014 unequal social outcomes, and tend to be prejudiced toward a variety of groups (Dovidio & Hebl, 2005;Pratto, Sidanius, Stallworth, & Malle, 1994). Aquino et al (2005) found that people high in social dominance orientation evaluated Black ratees more negatively than people with low social dominance orientation. This effect was stronger when the respondents believed that the Black ratee had been hired through an affirmative action process.…”
Section: Individual Differences Affecting Biasmentioning
confidence: 96%
See 1 more Smart Citation
“…Those high in social dominance orientation believe in group hierarchies and Downloaded by [Florida Atlantic University] at 07:42 18 November 2014 unequal social outcomes, and tend to be prejudiced toward a variety of groups (Dovidio & Hebl, 2005;Pratto, Sidanius, Stallworth, & Malle, 1994). Aquino et al (2005) found that people high in social dominance orientation evaluated Black ratees more negatively than people with low social dominance orientation. This effect was stronger when the respondents believed that the Black ratee had been hired through an affirmative action process.…”
Section: Individual Differences Affecting Biasmentioning
confidence: 96%
“…Brief, Dietz, Cohen, Pugh, and Vaslow (2000) found that only when White participants were given a business justification to discriminate (the boss's belief that the race composition of the sales force should match that of the customer base), did modern racism predict selection bias against Black applicants. Aquino, Stewart, and Reed (2005) suggested social dominance orientation as a factor in appraisal bias. Those high in social dominance orientation believe in group hierarchies and Downloaded by [Florida Atlantic University] at 07:42 18 November 2014 unequal social outcomes, and tend to be prejudiced toward a variety of groups (Dovidio & Hebl, 2005;Pratto, Sidanius, Stallworth, & Malle, 1994).…”
Section: Individual Differences Affecting Biasmentioning
confidence: 98%
“…Social dominance theory incorporates many theories of oppression to explain sources of group-based prejudice and discrimination (Aquino, Stewart & Reed, 2005). The theory presupposes that inequality is inevitable.…”
Section: Diversitymentioning
confidence: 99%
“…Stigmatization tends to compound the ingroup/out-group dynamics of social identity, thus amplifying the likelihood of religious bias against working with a Muslim among Christian perceivers. With respect to race and gender, management research has established perceptions of competence and attitudes toward interpersonal interactions as typical aspects of bias (Heilman et al 1992, Aquino et al 2005. These outcomes are critical to individual success and organizational effectiveness and there is reason to believe these biases may extend to religious differences.…”
Section: Stigma Theorymentioning
confidence: 98%
“…Two items analogous to those utilized by Aquino et al (2005) and Heilman et al (1992Heilman et al ( , 1998 were created to assess respondents' attitudes toward working with the hypothetical Muslim (or Christian) co-worker. The items were, "How do you think this individual would be as a group member?"…”
Section: Working Relationshipmentioning
confidence: 99%